THE PROCESS OF OSSEOINTEGRATION DURING DENTAL IMPLANTATION AND THE MODERN CONCEPT OF THE OSSEOINTEGRATION STIMULUS - Gubaev Mukhitdin Sarimsokovich (Лучшие интеллектуальные исследования, 2024)
To date, dental implantation has been successfully used in the planning of orthopedic rehabilitation in various defects of the dentition and bone tissue. Currently, the relevance of this method of dental treatment is used worldwide with a high prevalence of partial and complete absence of teeth and the need for patients to aesthetically, effectively restore the integrity of the dental system in conditions of increasing demands for aesthetics and comfort.